Environmental Management on Natural River Based on Water Quality Deterioration in Terengganu River Basin, Terengganu, Malaysia - Mohd Khairul Amri, Kamarudin; Nurul Hafizza, Mohd Amran; Noorjima, Abd Wahab; Muhammad Hafiz, Md Saad (2018)
This study is aimed to look at the level of water quality deterioration in Terengganu River Basin. Environmental management studies on the deterioration of water quality in Terengganu River Basin have been using data collection and analysis methods. The Gravimetric method was used to analysis the TSS measured in mg/L. 250 ml water samples was needed for each study area (each station). All preparation and preservation of the samples are in accordance with standard procedures provided by the American Public Health Society (APHA) and United States Environmental Protection Agency (USEPA). The results show that Terengganu River Basin is classified in level III that is contaminated. The Terengganu River Basin is contaminated at the downstream to the middle of the river due to anthropogenic activity. Moreover, the results indicate that the amount of AN and TSS is higher and is a major contributor to the deterioration of water quality in the Terengganu River Basin. Management of water resources should be improved and noted. This study has proposed several steps in managing water resources such as settlement of land use solutions, regulatory methods, river quality monitoring programs, minimizing waste, wall construction, the use of Geographic Information System (GIS) and legislative measures.